2004
DOI: 10.1200/jco.2004.09.160
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Human Telomerase Reverse Transcriptase Expression As Markers for Progression and Prognosis of Colorectal Carcinoma

Abstract: Telomeres in colorectal carcinoma tissue were significantly shorter compared with adjacent normal mucosa as an indication for extensive cell proliferation. The correlation with tumor stage and patient survival suggest that hTERT-mediated telomere stabilization may be critical for progression and prognosis of colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
168
5
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(197 citation statements)
references
References 29 publications
21
168
5
1
Order By: Relevance
“…However, the meaning of telomere length is a complicated subject. While it has been shown that telomere length correlates inversely, and telomerase activity directly, with malignancy in epithelial tumors, [6][7][8][9] only a couple of studies address this question in soft tissue tumors. 22,23 Bonatz et al measured telomere length in 107 uterine leiomyomas using a Southern blot method and found that telomeres were significantly shorter in tumoral tissue compared to adjacent uterine smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the meaning of telomere length is a complicated subject. While it has been shown that telomere length correlates inversely, and telomerase activity directly, with malignancy in epithelial tumors, [6][7][8][9] only a couple of studies address this question in soft tissue tumors. 22,23 Bonatz et al measured telomere length in 107 uterine leiomyomas using a Southern blot method and found that telomeres were significantly shorter in tumoral tissue compared to adjacent uterine smooth muscle.…”
Section: Discussionmentioning
confidence: 99%
“…However, since there is a 50% chance that the same X-inactivation could occur incidentally between two tumors, more cases should be analyzed using this method. Telomere shortening, a possible crucial event leading to chromosomal instability and development of malignancy, has been reported in multiple types of human cancer [6][7][8][9] and can be demonstrated with telomerespecific fluorescence in situ hybridization (FISH) probes.…”
mentioning
confidence: 99%
“…3B). Though previous studies have reported an association between hTERT expression levels and disease progression in colorectal cancer [47][48][49], these studies primarily looked at hTERT transcript levels. Here, 78% of colon tumours expressed hTERT protein, 8% of which had nuclear hTERT expression, similar levels of hTERT expression in colorectal tumours have been previously reported [50].…”
Section: Ruvbl2 Impacts Htert Activity and Associates With Htert Exprmentioning
confidence: 99%
“…For these reasons, numerous investigators have hypothesized that altered telomere length could predispose cells to possess the properties necessary to metastasize and cause recurrent disease, and thereby be a predictor of clinical outcome. [12][13][14][15][16][17][18][19][20][21][22][23][24] This concept is shown schematically in Figure 1.…”
mentioning
confidence: 99%
“…[8][9][10][11] This review summarizes the use of telomere length or its proxies, such as telomere content, as potential prognostic markers in solid tumors, a possibility that has been raised in the last decade by a number of investigators. [12][13][14][15][16][17][18][19][20][21][22][23][24] A corresponding comprehensive discussion of these promising developments has not yet been offered, in spite of the growing body of knowledge. Excluded from this discussion are numerous reports on the prognostic value of telomeres in hematological malignancies, a research area that, in contrast to solid tumors, has been addressed in more depth and previously reviewed.…”
mentioning
confidence: 99%